Connectors for electrical and electronic equipment. Product requirements. Circular connectors. Detail specification for B12 bayonet coupling connectors based on mating interfaces according to IEC 61076-2-101 and IEC 61076-2-109 Part 2-011, (19th August 2021) - British Standards Institution,
No abstract available